Transcriptomic, metabolomic, and ATAC-seq analysis reveal the regulatory mechanism of senescence of post-harvest tomato fruit - Guo, Susu; Ji, Yanhai; Zheng, Yanyan; Watkins, Christopher B.; Ma, Lili; Wang, Qing; Liang, Hao; Bai, Chunmei; Fu, Anzhen; Li, Ling; Meng, Demei; Liu, Mingchi; et al. (Frontiers in Plant Science, 2023)
Some physiological changes occurred during fruit storage, which involves the regulation of genes, metabolisms and transcription factors. Here, we compared two different varieties of tomato fruit (Solanum lycopersicum), namely ‘JF308’ (a normal tomato cultivar) and ‘YS006’ (a storable tomato cultivar), to determine difference of accumulated metabolites, gene expression, and accessible chromatin regions by metabolome, transcriptome, and ATAC-seq. A total of 1006 metabolites were identified in two cultivars. Sugars, alcohols, and flavonoids were more abundant in ‘YS006’ than ‘JF308’ during day 7, day14, and day 21 storage time, respectively. Differentially expressed genes, which involved in starch and sucrose biosynthesis were observed higher in ‘YS006’. ‘YS006’ had lower expression levels of CesA(cellulose synthase), PL (pectate lyase), EXPA(expansin) and XTH(xyloglucan endoglutransglucosylase/hydrolase) than ‘JF308’. phenylpropanoid pathway, carbohydrate metabolism and cell wall metabolism play important roles in prolonging the shelf-life of tomato fruit. ATAC-seq revealed that the TCP 2, 3, 4, 5 and 24 belong to basic helix-loop-helix factors class, are the most significant up-regulated transcription factors in J21 vs. Y21 (‘JF308’ was compared with ‘YS006’ on the day 21 of storage). The information on the molecular regulatory mechanisms and metabolic pathways of post-harvest quality changes in tomato fruit provides a theoretical foundation for slowing post-harvest fruit quality decay and loss, and has theoretical importance and application value in breeding for longer shelf life cultivars.